Aboutness (what-the-document-is-about): the first step of subject indexing and its use in everyday life (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The paper discusses the topic of aboutness as a central concept in the field of subject matter organization of knowledge and information and as the first step in the subject indexing process. Aboutness refers to determining what the document is about, what the document covers, or what its subject or topic is. The primary goal of the paper is to offer a definition, typology and understanding of the concept of aboutness, as well as a description of the existing procedures and methods of its determination, based on a detailed review of recent literature.Approach/methodology. The paper uses the method of detailed literature review and analysis in the field of subject indexing, as well as the methods of footnote chasing and citation searching in case of the review papers on the topic of aboutness.Findings. The review results showed there are several practical methods for determining the aboutness by Joudrey, Wilson, Langridge and Taylor, and several problems that may arise during this procedure.Originality/value. The ultimate aim is to exemplify the acquired knowledge and the results through their practical application in everyday life. It is precisely the exemplification of theoretical knowledge on aboutness that shows the originality of the present paper and at the same time contributes to its better understanding and determining both by information science and search engine optimization experts, journalists and website editors, as well as by the end users who search the Internet and assign their tags.
Keywords: aboutness; document topic; subject analysis; subject indexing